Correlation of cholecystokinin receptors with gallbladder contractility in patients with gallstones. - Upp, J R (1987)
The authors have previously identified two groups of patients with gallstones: those whose gallbladders contract the same as those of normal volunteers and show an increased sensitivity to endogenous cholecystokinin (CCK) ("contractors") and those whose gallbladders are relatively unresponsive ("noncontractors"). To define the mechanism responsible for these differences in contractility, the authors have measured CCK receptors on gallbladder muscle of patients with gallstones. Twenty-three patients with gallstones and 10 healthy volunteers (controls) fasted overnight. Simultaneous plasma samples for radioimmunoassay of CCK release and ultrasonographic measurements of gallbladder volume were obtained before and at intervals for 60 minutes after ingestion of Lipomul. Patients with gallstones had cholecystectomy, and CCK receptors were determined on cell membranes from gallbladder specimens by use of radiolabeled analogs of CCK-8-SO4. Histologic sections were graded for the degree of inflammation and scarring. Thirteen patients with gallstones were identified as contractors and 10 as noncontractors. Basal gallbladder volumes were not significantly different between patients in either group. The total integrated output of CCK for contractors was 1.6 +/- 0.2 ng X min/ml compared with 5.5 +/- 1.2 ng X min/ml for controls, while the integrated output for noncontractors was 11.1 +/- 2.1 ng X min/ml. Contractors had a higher number of CCK-binding sites (27.6 +/- 6.8 fmol/mg protein) than did noncontractors (4.8 +/- 1.0 fmol/mg protein). CCK receptors in gallbladders of all patients with gallstones correlated closely with gallbladder motility (y = 1.149, x = 0.624, r = 0.7, p less than 0.001). Although contractors had more mild inflammation and scarring, 40% of noncontractors had mild inflammation and scarring; there was no correlation. A decrease in CCK receptors may be an early event in the pathogenesis of gallstone formation by causing a decrease in gallbladder motility in some patients.